Reviewing the Evidence Base for Mental Health First Aid Is There Support for Its Use with Key Target Populations in California? - Wong, Eunice C. (RAND Corporation, 2015)
This report reviews the current state of evidence for Mental Health First Aid's effectiveness in key target populations, to help the California Mental Health Services Authority's planning for future prevention and early intervention activities.